Absorption and translocation of 2,4-D in plants of Memora peregrina - Mendonça, Cristiane Gonçalves de [UNESP]; Tornisielo, Valdemar Luis; Victoria Filho, Ricardo; Lacerda, André Luiz de Souza (My University, 2005)
The objective of this work was to evaluate absorption and translocation of the herbicide 2,4-D in plants of Memora peregrina. The herbicide 2,4-D was used alone with the formulation DMA 806 BR and associated with the herbicide picloram in the commercial product Padron. Levels of radioactivity on the treated leaves were determined in sample obtained after washing them with methanol and chloroform at different times after the application of the radiolabelled formulation (1, 2, 4, 8, 24, and 48 h). Translocation was evaluated by cutting plants between stem and root. The parts obtained were: root, stem, leaf treated, leaves above the leaf treated, leaves below the leaf treated, and leaf opposite of the leaf treated. These parts were weighted, dried, ground, burnt, and radioactivity in the samples was determined. The results suggest that the translocation of the radioactive herbicide 2,4-D was insignificant in plants of M. peregrina in the two treatments evaluated. Absorption of 14C 2,4-D in the treatment with DMA 806 BR and the mixture of DMA 806 BR plus Padron had the same behavior. These observations explain the inefficient control obtained with this herbicide in plant species under study.
Keywords: 2,4-D; Picloram; Translocation; Herbicides; Methanol; Radioactivity; Weed control; Herbicide formulation; Memora peregrina; 2,4 dichlorophenoxyacetic acid; chloroform; picloram; herbicide; translocation; weed control; nonhuman; plant leaf; plant root; plant stem; radioactivity; stem cutting; 2,4-Dichlorophenoxyacetic Acid; Carbon Radioisotopes; Pest Control; Plant Leaves; Chloroform; Weed Control; Memora; Peregrina